DAMPAK PEMBANGUNAN PROYEK PERUMAHAN CITRALAND BAGYA CITY TERHADAP PENGHASILAN MASYARAKAT DESA MEDAN ESTATE KECAMATAN PERCUT SEI TUAN - Evalina Pakpahan (Fakultas Ekonomi Universitas Tjut Nyak Dhien Medan, 2018)
Housing construction Citraland Bagya City lead changes and impacts to the community, especially the local community housing development Citraland Bagya Land, the villagers of Medan Estate Percut Sei Tuan districts, where people do the activity around the area of ​​development and getting the direct impact of such development. The impact of housing development can not only be detrimental to the community around the development of housing, but the housing development will bring new changes into the lives of people around the housing development, including changes in culture, socio-economic changes and changes in the geographical structure. This study used a qualitative approach with descriptive methods in order to understand in depth and find out how the development impacts of housing projects Citraland Bagya City against villagers in Medan Estate Percut Sei Sub district host. Data collection techniques in this study is the observation and in-depth interviews. The informants numbered 7 consists of traders around the building, village officials and villagers in Medan Estate. To enrich the data and information about the public perception of the impact of development Citraland Bagya City, also used data collection techniques by questionnaire with sample of 68 people. Citrland Bagya City housing construction provides impact and changes to society, there are changes in society to addressing the development Citraland Bagya City that community can increase the value of integrity. Citraland Bagya City Development also provides many physical and non-physical impact, the physical impact is the damage to infrastructure, while the non-physical impacts that rising incomes that generate economic activity around the construction Citraland Bagya City.